Implikasi pencerobohan tanah tanah kerajaan dan cadangan penyelesaian - Othman, Asiah; Abdul Rahim, Razani; Husin, Khadijah (UTM, 2001)
Issues on land trespassers have always being discussed in the developing nation and our country is not the exceptional. The issue of trespassers whether in the urban or rural areas needs to be addressed as it reflects the inefficiency of the land administration system as well as the weaknesses in the enforcement unit. Besides that, the problems also lead to substantial losses to the state government due to huge amount of uncollected revenue. This happens because of the non-existence of legal right of ownership. The uncontrollable activities of trespassers such as the squatter’s settlement, do not only creating an eyesore but its unplanned existence have les to other issues like pollution and social problem. This study is undertaken after realising the loss that the state government has incurred and it tries to show the impact of squatters around the city of Johor Bahru. Based on the field study as well as data collected from various government agencies, the study reveals that there is a negative impact. The squatter settlements are mostly potential land for various uses. Hence, the areas affected could be developed and fetch a high market values. Based on calculation it is estimated that the state government has lost revenue as the government fail to collect the quit rent, premium and charges. Briefly speaking the study estimated that state government of Johore has lost around RM 44 million per annum in terms of revenue and RM 198 million in terms of potential land values. It is hope that the findings could make the sate government aware of the substantial losses and appropriate measures should be taken.